Rendering human skin using a multi-layer reflection model - Li, Ling; Ng, C. (World Scientific and Engineering Academy and Society (WSEAS), 2009)
A key element to creating realistic images is the appearance of surfaces. In order to overcome the artificial look of synthetic humans, human skin has to be modelled in all its variety. A new physically-based skin reflection model is presented in this paper to render a diverse selection of skin complexions. The reflection model is based on steady-state light transport theory in multi-layered skin tissue. A three-layer simulation model has been developed to capture the effect of natural sebum on skin appearance. Sebum is found over most parts of the body, causing skin to look more specular, depending on the viewing conditions. Optical and geometric properties are used as control parameters to influence the surface reflection and subsurface scattering of light within the three layers. The resultant reflection consists of the specular reflection due to the Fresnel effect, as well as the diffuse reflection from subsurface scattering. The Monte Carlo method isused to simulate the propagation of light in skin tissue. Various effects like scattering, absorption, reflection and transmission have been taken into account. The bi-directional reflectance distribution function (BRDF) obtained from the simulation is used to render the appearance of human skin. Comparisons between the simulated BRDF results and experimental measurements show that the physical simulation is highly realistic.